Critical thinking and lexical cohesion of ESL learners’ academic writing / Vivian T. Stephen - Vivian, T. Stephen (2018)
This study investigated students’ use of lexical cohesion in writing and how it reflects the critical thinking. The study aims to: 1) determine the frequency of each type of lexical cohesion, i.e reiteration and collocation used by participants in writing, 2) determine the students’ critical thinking abilities by using the content analysis tool established by Newman et .at in 1995 and to 3) delve into the relationship, if any, the use of lexical cohesion in reflecting the critical thinking performance of participants. The lack of the studies which focused on the language use and how it might reflect the critical thinking of its user motivated the researcher to undertake this study. Participants of the study were Sixth Formers of a National type secondary school located in Klang Valley. A mixed method data analysis method was adopted for this study. Data was collected from the participants via a writing task given during their English lesson in school. Overall, 18 written samples were collected and used as the source of data of this study. Halliday and Hasan 1976) Taxonomy of Lexical Cohesion and the Newman et. al (1995) content analysis scheme were adopted to analyse the data and these two models provided quantitative results. In order to investigate the pattern of relationship between the use of lexical and critical thinking performance, a qualitative data analysis approach was used to study the written samples of proficient and less proficient students where the use of reiteration and collocation appeared and how the use of them might reflect the critical thinking performance of the proficient and less proficient students. Based on the Halliday and Hasan (1976) Taxonomy of Lexical Cohesion, it was found that reiteration was the most frequently used lexical cohesion device by less proficient students and collocation was the most frequently used lexical cohesion device by proficient students. In addition, after coding the data using The Newman et. al 1995) content analysis scheme, it was found that the proficient students who used significantly more collocations reflected their critical thinking ability in terms of being able to include relevant (R+ positive critical thinking indicator), clear (AC+ positive critical thinking indicators, novel (N+ positive critical thinking indicator) and justified (JS+ positive critical thinking indicator} input into their writing. On the other hand, less proficient students who used significantly more reiteration as in repetitions, reflected their critical thinking ability in terms of being able to include only irrelevant (R- negative critical thinking indicator), confused statements (AC- negative critical thinking indicators, false or trivial leads (N- negative critical thinking indicator) input into their writing. The ultimate purpose of this study is by understanding the pattern of relationship is between lexical cohesion and critical thinking is writing can enhance teaching syllabus, materials and evaluation methods for the teaching of critical thinking in academic writing.